Asthma and COVID-19: lessons learned and questions that remain. (2nd November 2021) - Howell, Daniel; Verma, Hannah; Ho, Kam Sing; Narasimhan, Bharat; Steiger, David; Rogers, Linda
ABSTRACT: Introduction: Asthma is one of the most common chronic diseases worldwide. As a disease of the respiratory tract, the site of entry for the SARS-CoV-2 virus, there may be an important interplay between asthma and COVID-19 disease. Areas covered: We report asthma prevalence among hospitalized cohorts with COVID-19. Those with non-allergic and severe asthma may be at increased risk of a worsened clinical outcome from COVID-19 infection. We explore the epidemiology of asthma as a risk factor for the severity of COVID-19 infection. We then consider the role COVID-19 may play in leading to exacerbations of asthma. The impact of asthma endotype on outcome is discussed. Lastly, we address the safety of common asthma therapeutics. A literature search was performed with relevant terms for each of the sections of the review using PubMed, Google Scholar, and Medline. Expert opinion: Asthma diagnosis may be a risk factor for severe COVID-19 especially for those with severe disease or nonallergic phenotypes. COVID-19 does not appear to provoke asthma exacerbations and asthma therapeutics should be continued for patients with exposure to COVID-19. Clearly much regarding this topic remains unknown and we identify some key questions that may be of interest for future researchers. uf0001